The effect of incorporating ionic liquid into polyethersulfone-SAPO34 based mixed matrix membrane on CO2 gas separation performance - Mohshim, D.F. (Elsevier, 2014)
The present study was conducted to investigate the effect of incorporating ionic liquid into flat sheet polyethersulfone-SAPO-34 mixed matrix membrane on the performance of CO2 separation. This was achieved by blending the ionic liquid emim(Tf2N), at different concentrations, with polymer-filler solution using solvent evaporation method. All fabricated membranes were characterized by field emission scanning electron microscopy and thermo gravimetric analysis. The membranes were observed to have dense structure as indicated by FESEM and lower polymer degradation temperature from TGA. The performance of CO2/CH4 separation of the new ionic liquid incorporated membranes was compared against that of pure mixed matrix membrane at pressures ranging from 10 to 30 bars. The experimental results show that the incorporation of ionic liquid into PES-SAPO-34 membrane resulted in more efficient CO2 separation. However, the permeance decreased when the pressure increased. The ideal CO2/CH4 selectivity determined from this study with the highest ionic liquid concentration is 62.6 as compared to 20.7 of pure mixed matrix membrane. This significant improvement of CO2/CH4 selectivity indicates that the ionic liquid can be used to enhance CO2 separation from CO4/CH4 mixture. Â© 2014 Elsevier B.V. All rights reserved.